Implementasi Kebijakan Disiplin Pegawai Negeri Sipil di Sekretariat DPRD Provinsi Sulawesi Utara - Sultan, Iin Inriani; Rompas, Sonny; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT To realize the discipline of civil servants UU.NO.43 1999 mandates the need enactment of government regulations regarding the discipline of civil servants. In connection with it will emerge Government Regulation No. 53 of 2010 on Discipline of Civil Servants civil service discipline. This study is intended to engetahui bagamana Impementasi the policy in Parliament Secretariat North Sulawesi, and the extent of the impact of the implementation of that policy to increase employee discipline. This study uses research kualtatif.informan taken from elements of leadership and the elements of staff / executive secretariat in the northern Sulawesi Provincial Parliament, entirely as many as 15 people informer. Insrumen in this study is the researchers themselves, while collecting data using techniques of data wawancara.analisis dilaukan with anaisis techniques Qualitative interactive model of Miles and Humbernann . research results conclusions: (1) Implementation of policy discipline PNS (PP.53 in 2010) has been done with good views of pnting dimension of public policy implementation model of Edward III, kususnya communication factor (socialization) policies, and disiposisi (koitmen and consistency ) implementing the policy. In concrete policy implementation PNS discipline shown by some reality; socialization rules of discipline, commitment and leadership to menerepkan mengakan disciplinary regulations, adnya efforts to raise awareness of employees to implement the provisions of the discipline as well as creating a culture of discipline, and the enforcement of disciplinary punishment consistently; (2) Implementation of policy discipline has given a positive dampa to increased discipline seen from increased adherence and provision of personnel to the provisions concerning the obligations and prohibitions applicable to civil servants Yng sebagaiman stipulated in the PP. 53 out of 2010. Based on the conclusion of the study put forward suggestions: (1) the implementation of civil service discipline policy should be more emphasis on the progressive increase in awareness that will manifest pure discipline; (2) the employee should be encouraged to have a high commitment and consistency in applying the rules of discipline of civil servants. Keywords: Policy Implementation, PNS Discipline Policy